2004
DOI: 10.1520/jfs2003088
|View full text |Cite
|
Sign up to set email alerts
|

Population Affinities of 19th Century Cuban Crania: Implications for Identification Criteria in South Florida Cuban Americans

Abstract: Identification criteria, specifically discriminant function formulae derived from traditional craniometrics, currently used in South Florida for Cuban Americans and other “Hispanic” groups, are unsuitable to provide adequate biological profiles due to complex biological histories as well as widely diverse geographic origins. Florida's total population is approximately 16 million (15,982,378) individuals. Of the total population 2,682,715, or 16.8%, are self-identified as “Hispanic”. South Florida (herein defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
55
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 3 publications
1
55
0
1
Order By: Relevance
“…As a uniquely Hispanic cluster is not formed, these patterns attest to a high level of admixture and the complexity of the label, "Hispanic," which is often a very personal social, linguistic, and geographic construct (Taylor et al, 2012). This trend also helps to explain the well-known difficulties in, for example, the forensic literature, on producing useful classifications for the identification of individuals of Hispanic identity (Ross et al, 2004;Spradley et al, 2008;Tise et al, 2014).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…As a uniquely Hispanic cluster is not formed, these patterns attest to a high level of admixture and the complexity of the label, "Hispanic," which is often a very personal social, linguistic, and geographic construct (Taylor et al, 2012). This trend also helps to explain the well-known difficulties in, for example, the forensic literature, on producing useful classifications for the identification of individuals of Hispanic identity (Ross et al, 2004;Spradley et al, 2008;Tise et al, 2014).…”
Section: Discussionmentioning
confidence: 85%
“…However, from these results, we can foresee how making clear group divisions will increase in difficulty and the risk of individual-level misclassifications will similarly grow as we direct our analysis towards more admixed populations -here, from the Native American, to Black to Hispanic groups. Indeed, prior work has shown that discriminant function analysis delivers particularly poor results for persons of Hispanic identity in forensic contexts (Ross et al, 2004;Spradley et al, 2008;Tise et al, 2014). This should give us pause as demographic trends in the U.S. are shifting towards an increase in both minority and admixed populations (Jones and Bullock, 2012;Colby and Ortman, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Human cranial variation has been studied through many different methods and in many different population groups (e.g. ). It has been shown that the morphology of the cranium is able to reflect both genetic and environmental influences that contribute to variation in its morphology .…”
mentioning
confidence: 99%
“…The standards for allocating or differentiating closely related populations, Hispanics for example, are currently being addressed by numerous researchers using both traditional and modern threedimensional methods [6][7][8][9]. Recent studies have paid much attention to the problematic nature of using biologically meaningless terms such as ''Hispanic'', which ignore geographic heterogeneity throughout the New World [7,10,11].…”
mentioning
confidence: 99%
“…Recent studies have paid much attention to the problematic nature of using biologically meaningless terms such as ''Hispanic'', which ignore geographic heterogeneity throughout the New World [7,10,11]. Ross et al [7] demonstrated that some modern Cubans show a strong African affinity followed by a Spanish component and lacked an indigenous Amerindian biological affinity suggesting a complete replacement of the indigenous Cuban population. On the other hand, some Mexicans showed a different biological pattern entirely, lacking both the African and Spanish components, while showing a strong indigenous Amerindian affinity [10].…”
mentioning
confidence: 99%